Variation in the composition of muscovite and albite in a pegmatite dike near Yellowknife - Kretz, Ralph (Canadian Journal of Earth Sciences, 1970)
Regular and irregular variations were found in the concentration of elements in muscovite and albite in relation to the distance from margin to center of a pegmatite dike near Yellow knife. For example, the magnesium content of muscovite increases towards the center, iron decreases, and lithium varies irregularly.The distribution of sodium and potassium among muscovite, albite, and potassium feldspar is considered in relation to mineral reactions and phase equilibrium. Comparison with experimental data indicates that the pegmatite specimens attained near-equilibrium at approximately 450 °C.